2004
DOI: 10.1161/01.cir.0000117229.60628.2f
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Overload–Induced Myocardial Hypertrophy in Mice Does Not Require gp91 phox

Abstract: Background-Reactive oxygen species (ROS) may mediate pressure overload-induced myocardial hypertrophy. NADPH oxidase may be involved in this process, because its expression and activity are upregulated by pressure overload and because myocardial hypertrophy caused by a subpressor infusion of angiotensin is attenuated in mice deficient in the gp91 phox catalytic subunit of NADPH oxidase. Methods and Results-To test the role of NADPH oxidase-dependent ROS in mediating pressure overload-induced myocardial hypertr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
53
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 30 publications
9
53
1
1
Order By: Relevance
“…In contrast to angiotensin II-induced hypertrophy, the hypertrophic response to aortic banding was found to be similar in Nox2 knockout mice and wild-type controls both by our group [17] and by Maytin et al [63]. However, we found that aortic banding induced similar increases in myocardial NADPH oxidase activity in wild-type and Nox2−/− mice, which could be attributed to increased expression of Nox4 mRNA and protein levels [17].…”
Section: Cardiac Hypertrophysupporting
confidence: 60%
“…In contrast to angiotensin II-induced hypertrophy, the hypertrophic response to aortic banding was found to be similar in Nox2 knockout mice and wild-type controls both by our group [17] and by Maytin et al [63]. However, we found that aortic banding induced similar increases in myocardial NADPH oxidase activity in wild-type and Nox2−/− mice, which could be attributed to increased expression of Nox4 mRNA and protein levels [17].…”
Section: Cardiac Hypertrophysupporting
confidence: 60%
“…In contrast to the AngII infusion studies, morphological LVH and the associated rises in ANF mRNA in response to aortic banding were similar in NOX2 K/K and wild-type mice (Byrne et al 2003). Similar results have also been reported by an independent laboratory (Maytin et al 2004). However, we found that aortic banding significantly increased LV NADPH oxidase activity and in situ O $K 2 production not only in wild-type but also NOX2 K/K mice, which was probably the result of increased expression of NOX4 in the banded NOX2 K/K animals since NOX4 mRNA and protein were both found to be elevated.…”
Section: Involvement Of Nadph Oxidases In Lvh and Heart Failuresupporting
confidence: 88%
“…The potential role of gp91 phox in the heart has been studied in other models. Maytin et al have indicated that myocardial hypertrophy induced by chronic pressure overload after aortic constriction was also not affected in gp91 phox knockout mice (43). However, another study has shown the reduced cardiotoxicity following doxorubicin treatment in gp91 phox knockout mice (44).…”
Section: Discussionmentioning
confidence: 99%